(untitled) (Revista Educação, Artes e Inclusão, 2020)
This report reflects on a dance experience with a group of women welcomed in the Women’s Penance Psychological Sector of the city of Rennes, France and some health professionals from that space. This experience was lived and taught by the author in the year 2018. The text is nourished by reflections and notes taken from a logbook that accompanied her during this journey. In it is the trajectory of the construction of a common space, shaped by these bodies in transit. The text points to the hesitations, discoveries, surprises, questions and adversities of this experience. It also discusses the problems encountered within the unit and their respective tensions. In a chronological way, it proposes to the reader to share this experience that results in the transformation of those women who, gradually, were undoing some bonds, shells, protections to surrender to the dancing movement. It aims to reaffirm not only the potency of artistic practices in unusual social contexts, but also the importance of their applicability.